CLINICAL AND BIOCHEMICAL STUDY OF TETANUS - SUNANDA AMONKAR; CHITRA Y. DHUME; MITCHELLE MENEZES (International Journal of Pharma and Bio Sciences, 2013)
Tetanus is a medical condition characterized by a prolonged contraction of skeletal muscle fibersTetanospasmin is a neurotoxin which causes the symptoms of tetanus.It is a neurotoxin produced by gram positive bacterium Clostridium tetani.infection starts with wound contamination and steadily progresses causing muscle spasms known as “lock jaw Under the present study, all cases of tetanus admitted under the Department of Medicine of Goa Medical College from July 2008 to October 2010 were studied and analyzed. Following admission, a detailed history of the patients was taken, the patients were then thoroughly examined and clinical finding noted. At admission, all patients received tetanus toxoid injection and 3000IU of tetanus immunoglobulin. Appropriate treatment was given to patients who developed complications. At the end of the study, it was concluded that tetanus is more common in the rural areas, in younger males .Incubation period and period of onset are reliable indicators of severity of tetanus and prognosis. Grading of tetanus is very helpful in predicting the prognosis of tetanus and injection of intrathecal TIG probably influences the course of disease favorably.